The emerging role of Th1 cells in atherosclerosis and its implications for therapy - Chen, Jiaojiao; Xiang, Xuying; Nie, Lei; Guo, Xiaoqing; Zhang, Feng; Wen, Cheng; Xia, Yuanpeng; Mao, Ling (Frontiers in Immunology, 2023)
Atherosclerosis is a chronic progressive inflammatory disease of the large and medium-sized artery walls. The molecular mechanisms regulating the onset and progression of atherosclerosis remain unclear. T cells, one of the most common cell types in atherosclerotic plaques, are increasingly recognized as a key mediator in the pathogenesis of atherosclerosis. Th1 cells are one subset of CD4+ T helper cells of the adaptive immune system, which is characterized by the expression of the transcription factor T-bet and secretion of cytokines such as IFN-γ. Converging evidence shows that Th1 cells play a key role in the onset and progression of atherosclerosis. Besides, it serves as the central mediator to orchestrate the adaptive immune system. In this review, we aim to summarize the complex role of Th1 cells in atherosclerosis and propose novel Th1 cell-targeted interventions to prevent atherogenesis.